Past and present: Improving early childhood visual spatial abilities through traditional game cengkling - Nofrans Eka Saputra; Yun Nina Ekawati (Universitas Ahmad Dahlan, 2021)
Visual spatial abilities are essential in academic and everyday life. This study aimed to determine the impact of traditional game cengkling on early childhood visual spatial abilities. A quasi-experimental with pretest-posttest control group design was applied with 18 participants evenly divided into experimental and control groups. Participants in the experiment group were given traditional game cengkling with a modification on the visual spatial system such as visual perception, color perception, and space. A visual ability scale was used to collect the data both in pretest and posttest. Data were then analyzed with the independent sample t-test and the paired sample t-test. The results show a significant difference in visual spatial abilities on pretest and posttest scores in the experimental group. Whereas in the control group, no significant difference in visual spatial abilities was found. It can be concluded that the traditional game cengkling stimulates visual spatial abilities in early childhood.